Sewage sludge compost as an alternative source of phosphorus to rye in acidic sandy soil - Almási, Csilla; Orosz, Viktória; Tóth, Tímea; Henzsel, István; Demeter, Ibolya; Mansour, Mostafa M.; Makádi, Marianna (Acta Agraria Debreceniensis, 2024)
Today, the use of chemical fertilisers is significantly determined by their production and purchase costs, which are high. In contrast, phosphorus (P) is present in sewage sludge in a form that is easy for plants to absorb. Good quality sewage sludge compost (SSC) could contain a high quantity of P, together with other macro- and microelements and organic matter. The effect of regular SSC application on soil characteristics as well as plant parameters has been studied since 2003 in Nyíregyháza in a small plot experiment. Focusing on the P in the soil-plant system, our hypothesis was that SSC covers plants’ P demand through enhancing soil P content and its plant availability in the acidic sandy soil. The effect of the SSC was examined at the doses of 0, 9, 18, and 27 t ha-1 on rye as a test crop. Some soil chemical parameters (pH, soil organic matter - SOM, ammonium lactate (AL) extractable P2O5), and the relationship between plant development (green weight, shoot length), physiological parameters (SPAD index), plant shoot P content, and soil available P content were studied. The obtained data indicated that the SOM content, pH, and available P content of the treated plots increased as a result of the long-term applied SSC compared to the control. Measurement of the relative chlorophyll content showed a strong correlation with the available P content of the soil, but surprisingly less correlation with shoot P content was found. The results of plant biomass and soil P content proved that SSC could be used as a low-cost and good source of P for plants.